Peran Filsafat Ilmu Terhadap Perkembangan Hukum Islam - Lidinirrahman, Muh Saad Said (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Abstract Rational thinking in the philosophy of science allows Islamic law to be more open to updates and adjustments to the principles of universal justice. Thus, the role of philosophy of science in legal science is not only as a theoretical instrument, but also as a base for strengthening legal legitimacy amid the challenges of modernity and globalization. The philosophy of science plays a central role in building the epistemological, methodological, and ethical foundations for the development of legal science. In the perspective of Islamic law, the contribution of the philosophy of science appears to be in the strengthening of the rational legitimacy of law, the development of a contextualized method of ijtihad, as well as the enrichment of the discourse of Shariah maqashid. Therefore, the integration of philosophy of science in the development of Islamic law not only enriches the academic treasury but also ensures the social relevance of Islamic law in the modern era.